I have a question that occurred to me and has been bothering me, because maybe graphically it seems obvious but I don't know how to get there. It has to do with the distribution function and monotone rearrangment.

Given a bounded function $f\colon [a,b] \rightarrow \mathbb{R}$, the (right-continuous) distribution of $f$ is the function $D_{f}$ definded by

\begin{align} D_{f}(y):= \mu(\{t\in I\colon f(t)\leq y \}),\; \forall y\in [\inf f, \sup f]. \end{align}

$\mu$ denotes de Lebesgue-measure. The (left-continuous) rearrangment of $f$, denoted by $f^{\ast}$, is the function: \begin{align} f^{\ast}(t):= \inf\{y\in [\inf f, \sup f] \colon D_{f}(y)\geq t \},\; \forall t\in [0,b-a]. \end{align}

It turns out that $f^{\ast}$ is the left inverse function of $D_{f}$, moreover it is the generalized inverse. They are both monotone increasing functions. Here is my question:

Let $t'\in [0,b-a]$ be a point such that $f^{\ast}$ is discontinuous in $t'$, this means $D_{f}$ has a constant segment over $[y_{j},y_{j+1})$ of value $t'$, so

\begin{align} t' = D_{f}(y_{j}) = D_{f}(y), \; \forall y\in [y_{j},y_{j+1}). \end{align}

How can I proof that: \begin{align} \lim_{t\to t'^{+}} f^{\ast}(t) = y_{j+1} \end{align}

Clearly: \begin{align} \lim_{t\to t'^{-}} f^{\ast}(t) = f^{\ast}(t') = f^{\ast}(D_{f}(y_{j}))=y_{j}. \end{align}

I would appreciate your help very much! If I am not being clear on something or you need more details please let me know.

  • 1
    $\begingroup$ Cross-posted to Math.SE $\endgroup$
    – Glorfindel
    Nov 5, 2021 at 7:58
  • $\begingroup$ Do you have a response to the answer below? $\endgroup$ Nov 10, 2021 at 2:46

1 Answer 1


$\newcommand{\ep}{\varepsilon}$Let \begin{equation*} c:=\inf f,\quad d:=\sup f,\quad I:=[a,b],\quad F:=D_f, \end{equation*} so that \begin{equation*} F(y)=\mu(\{t\in I\colon f(t)\le y \})\quad \forall y\in[c,d]. \end{equation*} Also introduce the set \begin{equation*} E_t:=\{y\in[c,d]\colon F(y)\ge t\}\quad \forall t\in[0,b-a]. \end{equation*} Since $F$ is nondecreasing and right-continuous, for all $t\in[0,b-a]$ \begin{equation*} f^*(t)=\inf E_t=\min E_t,\quad E_t=[f^*(t),d], \end{equation*} and, for all $y\in[c,d]$, \begin{equation*} F(y)\ge t\iff y\ge f^*(t). \tag{1} \end{equation*}

Now take any $t'\in[0,b-a]$ such that $f^*$ is discontinuous at $t'$. Since $f^*$ is nondecreasing and left-continuous, we have $f^*(t'+)>f^*(t')$. So, $t'<b-a$, and for some real $\ep>0$ and all $t\in(t',b-a]$ we have $f^*(t)>\ep+f^*(t')$; so, by (1), $F(\ep+f^*(t'))<t$ for all $t\in(t',b-a]$ and hence $F(\ep+f^*(t'))\le t'$. On the other hand, again by (1), $F(f^*(t'))\ge t'$. Since $F$ is nondecreasing, it follows that $F(y)=t'$ for all $y\in[f^*(t'),\ep+f^*(t')]$. So, introducing
\begin{equation*} Y:=\{y\in[c,d]\colon F(y)=t'\}, \end{equation*} \begin{equation*} y_1:=\inf Y,\quad y_2:=\sup Y, \end{equation*} we do have $y_1<y_2$ and $F(y)=t'$ for all $y\in[y_1,y_2)$.

Moreover, for any $y\in[y_1,y_2)$ and any $t\in(t',b-a]$, we have $F(y)=t'<t$ and hence, once again by (1), $y<f^*(t)$. Letting here $y\uparrow y_2$ and $t\downarrow t'$, we get $f^*(t'+)\ge y_2$.

Suppose now that $f^*(t'+)\ne y_2$. Then for some real $\ep>0$ we have $f^*(t'+)>\ep+y_2$. So, for all $t\in(t',b-a]$ we have $f^*(t)>\ep+y_2$, whence, once again by(1), $t>F(\ep+y_2)$. So, $t'\ge F(\ep+y_2)\ge F(y_1)=t'$ and hence $F(\ep+y_2)=t'$, which contradicts the definition $y_2:=\sup Y$.

Thus, indeed $f^*(t'+)=y_2$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge that you have read and understand our privacy policy and code of conduct.

Not the answer you're looking for? Browse other questions tagged or ask your own question.